Kenaikan Harga Bahan Bakar Minyak (Bbm) Atas Nama Rakyat (Tinjauan Kritis Konsepsi Keadilan Sosial Ekonomi Ibnu Taimiyah) - Arin Setiyowati (Universitas Muhammadiyah Surabaya, 2019)
AbstractThe continue phenomenon of fuel prices increasing in Indonesia arealways both between the two sides (there are government andcommunity). Debating the agree side and disagree side of being the maincontents of the escort policies. But we know the socio-economicscondition of ‘tragic’ Indonesia be raised expenditures greater thanrevenues, while expenditure was only focused on subsidies ofenergywhich unfortunatelymore widely used by the upper middle classsociety rather than small communities. Besides external factors that affectthe pattern of the domestic politics of oil policy. In the position of theeconomic dilemma, the government apllying the economic logic of